The effect of binaural beat stimulation on sustained attention - Robison, Matthew K.; Obulasetty, Mohitha; Blais, Chris; Wingert, Kimberly M.; Brewer, Gene A. (Psychological research, 2022)
Binaural beats have been used as a way of modifying cognition via auditory stimulation. A recent meta-analysis suggests that binaural beat stimulation can have a positive effect on attention (Garcia-Argibay et al., Psychologische Forschung 83:1124–1136, 2019a, Psychological Research Psychologische Forschung 83:357–372, 2019b), with the sample-weighted average effect size being about .58. This is an intriguing and potentially useful finding, both theoretically and practically. In this study, we focus on sustained attention. We delivered beta-frequency (16 Hz) binaural beat stimulation during a sustained attention task. In “Experiment 1 ”, reaction times were faster under beat stimulation than control stimulation in a between-subjects design. However, the effect was modest in magnitude, and model comparisons using Bayes Factors were indiscriminate between including and excluding the effect from the model. We followed this initial experiment with two concurrently administered follow-up experiments. In “Experiment 2 ”, we added thought probes to measure any changes in task engagement associated with binaural beat stimulation. “Experiment 2 ” revealed a different effect from “Experiment 1 ”: participants in the binaural beat condition exhibited a shallower vigilance decrement. However, the beat stimulation did not affect the thought probes responses. Combining data across the two experiments indicated rather strong evidence against the hypothesis that beta-frequency binaural beats can augment sustained attention, either via a general speeding of responding or a mitigation of the vigilance decrement. Finally, in “Experiment 3 ”, we investigated whether pupillary measures of arousal and/or task engagement would be affected by binaural beat stimulation. There was no evidence for such effects. Overall, we did not observe any consistent evidence that binaural beat stimulation can augment sustained attention or its subjective and physiological correlates.